ChemInform Abstract: Unravelling a New Class of Chiral Organocatalyst for Asymmetric Ring‐Opening Reaction of meso Epoxides with Anilines. Issue 46 (18th November 2014) - Kumar, Manish; Kureshy, Rukhsana I.; Saravanan, S.; Verma, Shailesh; Jakhar, Ajay; Khan, Noor‐ul H.; Abdi, Sayed H. R.; Bajaj, Hari C.
Abstract The chiral sulfinamide based organocatalyst (I) is synthesized and applied to the asymmetric ring‐opening reaction of meso epoxides with anilines.